DRESS syndrome: an interaction between drugs, latent viruses, and the immune system - Criado, Paulo Ricardo; Ianhez, Mayra; Miot, Hélio Amante [UNESP]; Criado, Roberta Fachini Jardim; Talhari, Carolina; Müller Ramos, Paulo [UNESP] (Elsevier, 2025)
Drug-induced hypersensitivity syndrome, also known as DRESS syndrome, is a serious and potentially fatal reaction that occurs in response to prolonged use (generally between 14 and 60 days) of certain drugs, and which has no predilection for gender or age group. It is believed that DRESS syndrome has a genetic basis and results from the interaction between metabolites of certain pharmacological groups, reactivation of latent viruses (especially from the Herpesviridae family), and a cellular immune response. The classic manifestation of DRESS syndrome includes a generalized rash accompanied by fever, eosinophilia, lymphadenopathy, and systemic involvement such as hepatitis, nephritis, or pneumonitis. With the continuous increase in the availability of drugs and the aging of the population, there is a favorable scenario for the development of adverse drug reactions. Physicians should be prepared for the early diagnosis of DRESS syndrome, the identification and immediate suspension of the drug involved, and also manage systemic involvement, which may require prolonged immunosuppressive therapy. This article provides an update on the clinical, physiopathological and therapeutic aspects of DRESS syndrome.
Keywords: Drug eruption; Drug hypersensitivity syndrome; Drug-related side effects and adverse reactions; Eosinophilia; Substance and drug-induced liver disease